Positive electrode active material for sodium-ion battery, sodium-ion battery prepared from active material, battery module, battery pack and device
By doping specific metal cations into the O3-phase layered metal oxide positive electrode material and adopting co-precipitation and solid-phase sintering methods, the problem that the material is prone to irreversible phase transformation in the high voltage segment is solved, and the high specific capacity and long life are achieved.
Patent Information
- Application Number
- CN202510208719.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2019-09-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing O3-phase layered transition metal oxide positive electrode materials are prone to irreversible phase transition in the high voltage segment, resulting in poor cycle stability and difficult to take into account both high specific capacity and long life.
The positive electrode active material was prepared by co-precipitation and solid-phase sintering methods using O3-phase layered metal oxides doped with specific metal cations (such as Li+, Cu2+, Zn2+, Co2+, Ti4+), and sintered at a temperature of 850-920°C for 15-25 hours.
The structural stability and crystallization performance of O3-phase layered metal oxides can be improved, and good cycling and electrical properties can be maintained at high voltages, achieving a better balance of specific capacity and life.
Smart Images

Figure BDA0005285361310000161 
Figure HDA0005285361320000011 
Figure HDA0005285361320000012
Abstract
Description
[0001] This application is a divisional application of an invention patent application with an application date of September 27, 2019, application number 201910922651.9, and invention name "Positive electrode active material for sodium ion battery, sodium ion battery made of the active material, battery module, battery pack and device". Technical Field
[0002] The present invention belongs to the field of electrochemistry and relates to a positive electrode active material for a sodium ion battery, and in particular to a positive electrode active material for a sodium ion battery that is resistant to high voltage. The present invention also relates to a high-voltage sodium ion battery, a battery module, a battery pack and a device made of the positive electrode active material. Background Art
[0003] Since the 1970s, researchers have begun to pay attention to sodium-ion rechargeable battery technology. However, due to the successful commercialization of lithium-ion batteries, the research and development of sodium-ion batteries has been at a standstill for a long time. Since 2010, lithium-ion battery technology has faced challenges from high energy density requirements, cost, performance and safety. Sodium-ion rechargeable battery technology has once again become the focus of battery research. At present, sodium-ion battery technology has experienced explosive development from the development of positive and negative electrode materials, electrolytes, isolation membranes, to the design of new chemical / electrochemical systems.
[0004] Similar to lithium-ion batteries, the key factor restricting the performance of sodium-ion batteries is their cathode materials. Among the various cathode materials that have been widely studied, such as oxides, fluorides, sulfides, phosphates, pyrophosphates, metal-organic frameworks / metal hexanides, and organic compounds, transition metal oxide cathode materials with layered structures have received extensive attention due to their high theoretical capacity, high density, low cost, and ease of material preparation, becoming a highly potential cathode material for sodium-ion batteries.
[0005] According to the stable phase structure of layered structure oxides, they can be classified into P2-phase and O3-phase layered metal oxides. Among them, the O3-phase NaxMO2 (0.67 < X ≤ 1; M = one or more metals among Fe, Mn, Ni, etc.) has great advantages in both specific capacity and specific energy, and is considered to be a very promising cathode material for sodium-ion batteries. However, at present, no suitable commercial O3-phase layered transition metal oxide cathode material with high specific capacity and long life at an acceptable cost has been found. This is mainly because the O3-phase layered transition metal oxide cathode material has the problem of irreversible phase transformation in the high voltage range (>4.1V) in the existing electrolyte system. This weak high-voltage resistance makes the material prone to structural distortion during charge and discharge in the high voltage range, resulting in poor long-term cycle stability of the material. In order to improve the cycle performance of the cathode material containing O3-phase layered transition metal oxides, it is necessary to reduce the charge and discharge voltage of the material at the cost of sacrificing the specific capacity of the cathode material, which reduces the commercial value of this type of material.
[0006] Therefore, the battery industry needs an O3-phase layered metal oxide cathode active material suitable for high-voltage sodium-ion batteries that can balance both the specific capacity and cycle stability of the battery. Summary of the Invention
[0007] In view of this, in the first aspect of the present application, the present invention provides a cathode active material for a sodium-ion battery, which mainly contains an O3-phase layered metal oxide, and the O3-phase layered metal oxide has the following molecular formula:
[0008] Na a M b Ni c Fe d Mn e O 2±δ (Formula I)
[0009] In Formula I,
[0010] M is a metal cation different from Ni, Fe, and Mn; 0.67 < a < 1.1; 0 < b < 0.25, preferably 0.05 < b < 0.15; 0 < c < 0.3, preferably 0.05 < c < 0.25; 0 < b + c < 0.55; 0.45 < d + e < 1; and b + c + d + e = 1; 0 ≤ δ ≤ 0.1,
[0011] Among them, the metal cation is selected from at least one of Li + , Cu 2+ , Zn 2+ , Co 2+ , Ti 4+ and the like.
[0012] In some specific embodiments of the present invention, the positive electrode active material is obtained by: i) co-precipitating a Ni source and a Mn source in the presence of a complexing agent and a precipitant by a co-precipitation method to obtain a nickel-manganese metal salt precursor, and ii) solid-phase sintering the nickel-manganese metal salt precursor obtained in step i) with a Na source, a Fe source, and an M metal source to obtain a positive electrode active material containing an O3-phase layered metal oxide. Preferably, the sintering is performed at a temperature of 850-920° C. for 15-25 hours.
[0013] In the second aspect of the present application, the present invention also provides a battery comprising a positive electrode sheet, a negative electrode sheet, an isolation membrane and an electrolyte separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, wherein the positive electrode active material is the positive electrode active material according to the present invention, and the battery has a charging cut-off voltage of 4.2V or higher.
[0014] On the other hand, the present invention also provides a battery comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, wherein the positive electrode active material is the positive electrode active material according to the present invention, and the battery has a charging cut-off voltage of 4.5V or higher.
[0015] In a third aspect of the present application, the present application provides a battery module, which includes the sodium ion battery described in the second aspect of the present application.
[0016] In a fourth aspect of the present application, the present application provides a battery pack comprising the battery module described in the third aspect of the present application.
[0017] In a fifth aspect of the present application, the present application provides a device, comprising the sodium ion battery described in the second aspect of the present application, wherein the sodium ion battery is used as a power source for the device.
[0018] In the positive electrode active material for sodium ion batteries according to the present invention, the O3 phase layered metal oxide doped with specific metal cations has high structural stability. When used under high voltage, it can not only maintain good cycle performance, but also stably exert electrical performance. The inventors surprisingly found that when Li is doped in the O3 phase layered metal oxide, + , Cu 2 + 、Zn 2+ 、Co 2+ 、Ti 4+ When at least one of the 003 / I 104The O3 layered metal oxide has a better structure order and a stronger metal-oxygen (MO) bond. In addition or alternatively, the O3 layered metal oxide has a better crystal structure, which is a space group of The hexagonal crystal system has a large ratio of the unit cell parameter c to the unit cell parameter a. The material has excellent crystallization performance and an optimal layered structure. Metal oxides with such a structure can achieve good cycle performance when used at a higher voltage while stably exerting their electrical properties, which was difficult to foresee before this application.
[0019] The inventors of the present invention surprisingly found that the sintering temperature and sintering time have an effect on the properties of the O3 phase layered metal oxide. The Li-doped O3 layered metal oxide obtained by sintering at 900°C for 20 hours has a good + , Cu 2+ 、Zn 2+ 、Co 2+ 、Ti 4+ At least one (as M metal) of O3 layered metal oxide Na a M b Ni c Fe d Mn e O 2±δ It has particularly excellent specific capacity and cycle performance.
[0020] The details of one or more embodiments of the invention are set forth in the description which follows. Other features, objects, and advantages of the invention will become apparent from the description and claims.
[0021] definition
[0022] When describing the present invention, the use of quantifiers (especially in the context of the claims) should be construed to cover both the singular and the plural, unless otherwise indicated or clearly contradicted by the context.
[0023] Where a method is described as including or comprising specific process steps, it is contemplated that optional process steps not explicitly stated are not excluded from the method and that the method may also consist of or consist of the process steps involved.
[0024] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0025] In the context of O3-phase layered metal oxides, I(003) / I(104) is used to reflect the degree of mixing of sodium metal cations in the O3-phase layered metal oxide, where I(003) represents the peak intensity of the positive electrode active material at the (003) crystal plane, and I(104) represents the peak intensity at the (104) crystal plane. Generally, the larger the ratio of I(003) / I(104), the lower the degree of mixing of sodium metal cations in the O3-phase layered metal oxide, which means that the structural order of the O3-phase layered metal oxide is higher and the structure is more stable.
[0026] In the context of O3 phase layered metal oxides, the "ratio of the unit cell parameter c to the unit cell parameter a" is used to characterize the crystal structure of the O3 phase layered metal oxide. Generally, when the c / a ratio is greater than 5, the material is considered to be well crystallized and has a layered structure. The larger the ratio, the higher the proportion of the layered structure in the material, and the better the layered structure formed.
[0027] In the context of O3 phase layered metal oxides, "hexagonal system" refers to a crystal structure having the following unit cell parameters, wherein the unit cell parameters are a=b≠c, and α=β=90°, γ=120°.
[0028] In the context of the O3 phase layered metal oxide, "primary particles" refer to crystal particles of the O3 phase layered metal oxide, which are different from particles (secondary particles) formed by agglomeration of crystal particles.
[0029] The terms "preferred" and "preferably" refer to embodiments of the present invention that may provide certain benefits under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the recitation of one or more preferred embodiments does not mean that other embodiments are not useful, and is not intended to exclude other embodiments from the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an X-ray derivative spectrum of the positive electrode active material for a sodium ion battery according to Example 5 of the present invention.
[0031] Figure 2 The first charge and discharge curves of a button cell made of the positive electrode active material for a sodium ion battery according to Example 5 of the present invention at different voltages.
[0032] Figure 3 The cycle performance of button cells made of the positive electrode active material for sodium ion batteries of Example 5 of the present invention at different voltages.
[0033] Figure 4 This is a perspective view of one embodiment of a sodium ion battery.
[0034] Figure 5 yes Figure 4 Exploded diagram of .
[0035] Figure 6 This is a perspective view of one embodiment of a battery module.
[0036] Figure 7 It is a perspective view of one embodiment of a battery pack.
[0037] Figure 8 yes Figure 7 Exploded diagram of .
[0038] Fig. 9 It is a schematic diagram of one embodiment of a device using a sodium ion battery as a power source.
[0039] The reference numerals are described as follows:
[0040] 1 battery pack
[0041] 2 upper box
[0042] 3 lower cabinets
[0043] 4 battery modules
[0044] 5. Sodium-ion battery
[0045] 51 Shell
[0046] 52 electrode assembly
[0047] 53 Top cover assembly DETAILED DESCRIPTION
[0048] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the present invention, not all of them. Based on the embodiments of the present invention, all technical solutions obtained by conventional modifications or deformations of the present invention by ordinary technicians in this field fall within the protection scope of the present invention.
[0049] In a first aspect, the present invention provides a positive electrode active material for a sodium ion battery, which mainly comprises an O3-phase layered metal oxide having the following molecular formula:
[0050] Na a M b Ni c Fe d Mn e O 2±δ (Formula I)
[0051] In Formula I, M is a metal cation different from Ni, Fe, and Mn; 0.67 < a < 1.1; 0 < b < 0.25, preferably 0.05 < b < 0.15; 0 < c < 0.3, preferably 0.05 < c < 0.25; 0 < b + c < 0.55; 0.45 < d + e < 1; and b + c + d + e = 1; 0 ≤ δ ≤ 0.1, wherein the metal cation is selected from + , Cu 2+ , Zn 2+ , Co 2+ , Ti 4+ and at least one of them.
[0052] In an embodiment according to the present invention, the positive electrode active material for a sodium ion battery mainly comprises an O3-phase layered metal oxide. In other words, the O3-phase layered metal oxide accounts for the main part of the positive electrode active material. In one embodiment of the present invention, the positive electrode active material for a sodium ion battery contains 90 wt% or more of the O3-phase layered metal oxide relative to the total weight of the positive electrode active material, preferably 95 wt% or more of the O3-phase layered metal oxide, more preferably 98 wt% or more of the O3-phase layered metal oxide, still more preferably 99 wt% or more of the O3-phase layered metal oxide. Most preferably, the positive electrode active material for a sodium ion battery consists of the O3-phase layered metal oxide.
[0053] The inventors of the present invention surprisingly found that in the positive electrode active material for a sodium ion battery according to the present invention, the O3-phase layered metal oxide doped with specific metal cations has high structural stability, and when applied at a high voltage, it can not only stably exhibit its electrical properties, but also has significantly improved cycling performance. Without being bound by any theory, the applicant speculates that the reason is that after doping and modifying the O3-phase sodium nickel manganese iron oxide with specific kinds of metal elements, it can effectively inhibit the irreversible phase transformation (P3 - P3') of the material in the high voltage section (for example, > 4.1V), ensuring the structural stability of the material during the charge and discharge process, thereby achieving a better balance between capacity and cycling performance. The irreversible phase transformation (P3 - P3') in the high voltage section is mainly Ni 3+In the O3 phase layered metal oxide according to the present invention, the doped metal enhances the interaction between transition metal and oxygen (TM-O), especially the interaction between nickel and oxygen (Ni-O), which can effectively inhibit the Ni 3+ The JT effect is achieved, thereby suppressing the irreversible phase transition in the high voltage region.
[0054] In an embodiment of the present invention, the metal cation suitable for doping the O3 phase layered metal oxide is selected from Li + , Cu 2 + 、Zn 2+ 、Co 2+ 、Ti 4+ At least one of the following. A metal cation particularly suitable for doping an O3 phase layered metal oxide is Li + The doping of these specific types of metal cations is crucial to improving the structural stability of metal oxides. The inventors of the present invention surprisingly found that the O3-phase layered metal oxides doped with these specific types of metal cations are superior to those doped with other metal cations (such as Mg) disclosed in the prior art. 2+ ) doped O3 phase layered metal oxide has improved structural stability. As a result, the O3 phase layered metal oxide obtained according to the present invention shows significantly better electrical and kinetic properties when used under high voltage.
[0055] The use of the above specific types of metal cations for doping enhances the interaction between transition metals and oxygen (TM-O) in the O3 phase layered metal oxide, which is reflected in the I(003) / I(104) parameter. In some embodiments of the present invention, the I(003) / I(104) of the O3 phase layered metal oxide in the X-ray diffraction spectrum is ≥0.62, wherein I(003) represents the (003) crystal plane peak intensity of the O3 phase layered metal oxide, and I(104) represents the (104) crystal plane peak intensity of the O3 phase layered metal oxide. I(003) / I(104) reflects the degree of mixing of sodium metal cations in the O3 phase layered metal oxide. Preferably, I(003) / I(104) of the O3 phase layered metal oxide in the X-ray diffraction spectrum is greater than or equal to 0.7, preferably greater than or equal to 0.75, more preferably greater than or equal to 0.8, even more preferably greater than or equal to 0.85, even more preferably greater than or equal to 0.9, but not higher than 1.5, not higher than 1.4, not higher than 1.3, not higher than 1.25, and not higher than 1.2.
[0056] Moreover, the use of the above specific types of metal cations for doping also enhances the crystallization properties of the O3 phase layered metal oxide, which is reflected in the ratio of the unit cell parameter c to the unit cell parameter a. In some embodiments of the present invention, the O3 phase layered metal oxide is a space group of Hexagonal system, wherein the ratio of the unit cell parameter c to the unit cell parameter a is ≥5, preferably ≥5.5. Preferably, the c / a ratio of the O3 phase layered metal oxide is greater than or equal to 5.6, or greater than or equal to 5.7, or greater than or equal to 5.8, or greater than or equal to 5.9, or greater than or equal to 6.0, or greater than or equal to 6.1, or greater than or equal to 6.2, or greater than or equal to 6.3, or greater than or equal to 6.4, or greater than or equal to 6.5, or greater than or equal to 6.6, or greater than or equal to 6.7, or greater than or equal to 6.8, or greater than or equal to 6.9, or greater than or equal to 7.0, but not higher than 9.0, not higher than 8.5 or not higher than 8.0.
[0057] In some preferred embodiments of the present invention, the I(003) / I(104) of the O3 phase layered metal oxide in the X-ray diffraction spectrum is ≥0.62, preferably between 0.67 and 1.5, and the O3 phase layered metal oxide is a space group of The hexagonal crystal system of the present invention is characterized in that the ratio of the unit cell parameter c to the unit cell parameter a is ≥ 5, preferably ≥ 5.5. The O3 phase layered metal oxide has particularly excellent structural stability and thus exhibits particularly excellent electrical and dynamic properties when used at high voltage.
[0058] Preferably, the primary particles of the O3 phase layered metal oxide according to the present invention are of a lamellar structure. In some embodiments of the present invention, the grain size of the primary particles is between 0.05 microns and 15 microns, preferably between 0.1 microns and 5 microns, for example, 0.2 microns, 0.3 microns, 0.4 microns, 0.5 microns, 0.6 microns, 0.7 microns, 0.8 microns, 0.9 microns, 1 micron, 1.5 microns, 2 microns, 2.5 microns, 3 microns, 3.5 microns, 4 microns, 4.5 microns or 4.8 microns.
[0059] Preferably, the compaction density of the positive electrode active material for sodium ion batteries according to the present invention under a pressure of 8 tons is between 1.5 g / cm 3 and 4.5g / cm 3 between, preferably between 2.5 g / cm 3 and 4g / cm 3 between.
[0060] In some embodiments of the present invention, the positive electrode active material is obtained by:
[0061] i) in the presence of a complexing agent and a precipitant, a Ni source and a Mn source are co-precipitated by a co-precipitation method to obtain a nickel-manganese metal salt precursor, and
[0062] ii) solid-phase sintering the nickel-manganese metal salt precursor obtained in step i) with a Na source, an Fe source and an M metal source to obtain a positive electrode active material comprising an O3-phase layered metal oxide.
[0063] The inventors of the present invention have found that, during the preparation of the positive electrode active material, the sintering temperature and sintering time will affect the electrical properties and cycle performance of the positive electrode active material.
[0064] The sintering temperature has a great influence on the performance of the material. This is mainly because when the sintering temperature is lower than the optimal sintering temperature, the reaction is incomplete, and it is easy to generate amorphous materials. The crystallization performance of the material is not good, and it contains impurities, which has a great influence on the electrochemical properties of the material. However, with the increase of the sintering temperature, the diffusion coefficient of the material increases, which promotes the diffusion of ions and vacancies, the material transfer process such as particle rearrangement, which is conducive to obtaining products with high crystallinity. Therefore, it is beneficial to increase the calcination temperature appropriately for the reaction. However, if the temperature is too high, it is easy to generate oxygen-deficient compounds and promote secondary recrystallization. At the same time, the grains of the material become larger and the specific surface area becomes smaller, which is not conducive to the removal and embedding of sodium ions in the material. Therefore, in an embodiment of the present invention, the sintering is carried out at a temperature of 850-920°C, preferably at a temperature of 890-910°C, more preferably at a temperature of 895-905°C, and most preferably at a temperature of 900°C.
[0065] The sintering time will also have an impact on the electrochemical properties of the material. With the increase of the sintering time, ions and vacancies have enough time to carry out material transfer processes such as diffusion and particle rearrangement, which is conducive to obtaining a product with a more stable structure. Therefore, it is beneficial to appropriately extend the sintering time for the reaction. However, a sintering time that is too long is economically disadvantageous and will not significantly improve the structural stability of the product. Therefore, in an embodiment of the present invention, the sintering is carried out for 15-25 hours, preferably for 17-22 hours, more preferably for 19 to 21 hours, and most preferably for 20 hours.
[0066] In the preparation process of the positive electrode active material for sodium ion battery according to the present invention, any Ni source, Mn source, Na source, Fe source, M metal source known to those skilled in the art for preparing positive electrode active materials for secondary batteries can be used. In an embodiment of the present invention, one or more of sulfate, carbonate, metal oxide, phosphate, nitrate, metal hydroxide or metal halide can be used as raw materials.
[0067] In the preparation process of the positive electrode active material for sodium ion battery according to the present invention, a complexing agent can be used. The complexing agent is one or more mixed solutions of ammonia water, ammonium bicarbonate, ammonium sulfate, ammonium carbonate, citric acid and disodium ethylenediaminetetracarboxylate.
[0068] In the process of preparing the positive electrode active material for sodium ion battery according to the present invention, a precipitant may be used, wherein the precipitant is a mixed solution of one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.
[0069] As described above, the positive electrode active material containing the O3 phase layered metal oxide according to the present invention has excellent structural stability and is suitable for use in a high voltage range.
[0070] Next, a sodium ion battery according to a second aspect of the present invention is described.
[0071] Figure 4 It is a perspective view of one embodiment of the sodium ion battery 5 . Figure 5 yes Figure 4 Exploded view of the Figures 4 to 5 The sodium ion battery 5 includes a shell 51, an electrode assembly 52, a top cover assembly 53 and an electrolyte (not shown).
[0072] The electrode assembly 52 is accommodated in the housing 51. The number of electrode assemblies 52 is not limited, and can be one or more. The electrode assembly 52 includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator separates the positive electrode sheet from the negative electrode sheet. The electrolyte is injected into the housing 51 and impregnates the electrode assembly 52, which includes, for example, a first electrode sheet, a second electrode sheet, and a separator.
[0073] Note that Figure 1 The sodium ion battery 5 shown is a can-type battery, but is not limited thereto. The sodium ion battery 5 may be a pouch-type battery, that is, the housing 51 is replaced by a metal plastic film and the top cover assembly 53 is removed.
[0074] Therefore, the second aspect of the present invention provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte spaced between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material is a positive electrode active material according to the present invention, and the battery has a charge cut-off voltage of 4.2V or higher. The sodium ion battery has an initial discharge specific capacity of 120mAh / g at a voltage of 2.0-4.2V and a capacity retention rate of 87% or higher after 100 cycles at 1C.
[0075] Another aspect of the present invention provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material is a positive electrode active material according to the present invention, and the battery has a charge cut-off voltage of 4.5V or higher. The sodium ion battery has an initial discharge specific capacity of 150mAh / g at a voltage of 2.0-4.5V and a capacity retention rate of 80% or higher after 100 cycles at 1C.
[0076] In the sodium ion battery according to the present invention, the positive electrode sheet containing the positive electrode active material has a certain compaction density. Preferably, the compaction density TD of the positive electrode sheet is 1.5≤TD≤4.0, preferably 2.0≤TD≤4.0. When the compaction density of the sheet is too low, it is not conducive to improving the volume energy density of the sheet. When the compaction density is too high, it is not conducive to the full contact of the electrolyte of the material and the electrochemical performance of the material.
[0077] When the positive electrode active material and the hard carbon negative electrode material form a sodium ion battery according to the present invention, the average particle size ratio of the positive and negative electrode materials is 0.2
[0078] The present invention has no particular limitation on the method for preparing the sodium ion battery, and a technical solution for preparing a sodium ion battery from a positive electrode active material well known to those skilled in the art may be adopted.
[0079] Next, a battery module according to the third aspect of the present application is described.
[0080] Figure 6 It is a perspective view of one embodiment of the battery module 4 .
[0081] The battery module 4 provided in the third aspect of the present application includes the sodium ion battery 5 described in the second aspect of the present application.
[0082] Reference Figure 6 The battery module 4 includes a plurality of sodium ion batteries 5. The plurality of sodium ion batteries 5 are arranged in a longitudinal direction. The battery module 4 can be used as a power source or an energy storage device. The number of sodium ion batteries 5 in the battery module 4 can be adjusted according to the application and capacity of the battery module 4.
[0083] Next, a battery pack according to a fourth aspect of the present application is described.
[0084] Figure 7 It is a perspective view of one embodiment of the battery pack 1 . Figure 8 yes Figure 7 Exploded diagram of .
[0085] The battery pack 1 provided in the fourth aspect of the present application includes the battery module 4 described in the third aspect of the present application.
[0086] Specifically, refer to Figure 7 and Figure 8 The battery pack 1 includes an upper case 2, a lower case 3 and a battery module 4. The upper case 2 and the lower case 3 are assembled together to form a space for accommodating the battery module 4. The battery module 4 is placed in the space of the upper case 2 and the lower case 3 assembled together. The output pole of the battery module 4 passes through one or both of the upper case 2 and the lower case 3 to supply power to the outside or charge from the outside. The number and arrangement of the battery modules 4 used in the battery pack 1 can be determined according to actual needs.
[0087] Next, the device according to the fifth aspect of the present application is described.
[0088] Fig. 9 It is a schematic diagram of one embodiment of a device using a sodium ion battery as a power source.
[0089] The device provided in the fifth aspect of the present application includes the sodium ion battery 5 described in the second aspect of the present application, and the sodium ion battery 5 can be used as a power source for the device. Fig. 9In the embodiment, the device using the sodium ion battery 5 is an electric vehicle. Of course, it is not limited to this. The device using the sodium ion battery 5 can be any electric vehicle other than an electric vehicle (such as an electric bus, an electric tram, an electric bicycle, an electric motorcycle, an electric scooter, an electric golf cart, an electric truck), an electric ship, an electric tool, an electronic device and an energy storage system. The electric vehicle can be an electric pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. Of course, depending on the actual use form, the device provided in the fifth aspect of the present application may include the battery module 4 described in the third aspect of the present application. Of course, the device provided in the fifth aspect of the present application may also include the battery pack 1 described in the fourth aspect of the present application.
[0090] In one embodiment of the present invention, a button cell is prepared as follows:
[0091] 1. Preparation of positive electrode
[0092] The positive electrode active material according to the present invention, conductive carbon, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of N-methylpyrrolidone (abbreviated as NMP) solvent at a weight ratio of 80:15:5 to form a uniform positive electrode slurry; the slurry is coated on the positive electrode current collector carbon-coated Al foil, and after drying, it is punched into small discs with a diameter of 14 mm.
[0093] 2. Preparation of electrolyte
[0094] Dissolve an equal volume of ethylene carbonate in propylene carbonate, and then evenly dissolve an appropriate amount of sodium perchlorate in the mixed solvent for later use.
[0095] 3. Negative electrode: Use metallic sodium sheets.
[0096] 4. Isolation membrane: There is no special choice, glass fiber or non-woven fabric can be used.
[0097] 5. Preparation of button battery:
[0098] Stack the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and inject the prepared electrolyte into the battery cell to complete the preparation of the button battery.
[0099] Example
[0100] In order to facilitate the understanding of the present invention, the present invention lists the following embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0101] Test Method
[0102] X-ray diffraction and data refinement
[0103] Powder sample X-ray diffractometer (XRD, Bruker D8) was used to obtain powder diffraction data; the X-ray source was CuKα, the operating voltage was 40kV, and the current was 40mA. The sample scanning angle range was 10-80 degrees, and the step size was selected as 0.02 degrees. VESTA was used to construct the basic structure of the synthesized material, and then the GENERAL STRUCTURE ANALYSIS SYSTEM software (GSAS) was used to refine the XRD spectrum. The atomic parameters in the structure, the peak shape parameters used for fitting, and the instrument parameters were adjusted by the least squares method to minimize the weighted residual variance factor Rwp of the entire spectrum. After the refinement meets the requirements, the structural data is exported and analyzed and plotted using VESTA.
[0104] Grain size
[0105] The grain size of the positive electrode active material was determined by X-ray diffractometer.
[0106] Compacted density of positive electrode film
[0107] Step 1): Weigh the positive electrode film layer mass using a standard balance and measure the positive electrode film coating area using a ruler, and then calculate the positive electrode film layer unit area mass (g / cm 2 ).
[0108] Step 2): According to the compaction density D (in g / cm 3 = mass per unit area of positive electrode film (g / cm 2 ) / positive electrode film thickness (cm), and the positive electrode film compaction density D is calculated, where the positive electrode film thickness can be measured by a micrometer.
[0109] First discharge specific capacity of sodium-ion batteries at high voltage
[0110] At 2 to 4.2 V, charge to 4.2 V at 0.1 C, let stand for 2 minutes, the charge capacity at this time is recorded as C0, and then discharge to 2 V at 0.1 C. The discharge capacity at this time is the first discharge specific capacity at 2-4.2 V, recorded as D0.
[0111] Similarly, at 2 to 4.5 V, charge to 4.5 V at 0.1 C, let stand for 2 minutes, the charge capacity at this time is recorded as C0, and then discharge to 2 V at 0.1 C. The discharge capacity at this time is the first discharge specific capacity at 2-4.5 V, recorded as D1.
[0112] Cycling performance of sodium-ion batteries at high voltage
[0113] At 25°C, the sodium ion battery is first charged at a constant current of 1C to a voltage of 4.2V, and then discharged at a constant current of 1C to a voltage of 2.0V. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The sodium ion battery is subjected to 100 cycles of charge / discharge tests according to the above method, and the discharge capacity of the 100th cycle is detected.
[0114] Capacity retention rate (%) of the sodium ion battery after 100 cycles = (discharge capacity of the sodium ion battery after 100 cycles / discharge capacity of the sodium ion battery in the first cycle) × 100%.
[0115] Similarly, at 25°C, the sodium ion battery is first charged at a constant current of 1C to a voltage of 4.5V, and then discharged at a constant current of 1C to a voltage of 2.0V. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The sodium ion battery is subjected to 100 cycles of charge / discharge tests according to the above method, and the discharge capacity of the 100th cycle is detected.
[0116] Capacity retention rate (%) of the sodium ion battery after 100 cycles = (discharge capacity of the sodium ion battery after 100 cycles / discharge capacity of the sodium ion battery in the first cycle) × 100%.
[0117] Preparation of positive electrode active materials
[0118] First, NiSO4·6H2O and MnSO4·H2O are used as Ni source and Mn source, ammonia water is used as complexing agent, and NaOH is used as precipitant to prepare nickel manganese hydroxide precursor by coprecipitation method. Then, as shown in Table 1 below, Na2CO3, Fe3O4, salt or oxide containing doping element M and nickel manganese hydroxide precursor are fully ground and placed in a tube furnace for sintering at a specific temperature for a period of time, thereby obtaining the layered metal oxide Na containing O3 phase as shown in Table 1. a M b Ni c Fe d Mn e O 2±δ of positive electrode material.
[0119] As a control, the positive electrode active materials of Comparative Examples 1-4 were prepared by the above method, except that Comparative Examples 1-3 did not contain salt or oxide of the doping element M, and Comparative Example 4 was doped with Mg oxide.
[0120] According to the above test section, the ratio of I003 / I104 and the ratio of unit cell parameter c / a of the positive electrode active material of the present invention and the positive electrode active material for reference were measured, and the results are summarized in the following Table 1.
[0121] Manufacturing of sodium-ion batteries
[0122] 1. Preparation of positive electrode
[0123] The positive electrode active material of the present invention and the positive electrode active material for control are mixed with conductive carbon and binder polyvinylidene fluoride (PVDF) in an appropriate amount of N-methylpyrrolidone (abbreviated as NMP) solvent in a weight ratio of 80:15:5, and stirred to form a uniform positive electrode slurry; the slurry is coated on the carbon-coated Al foil of the positive electrode current collector, and after drying, it is punched into small discs with a diameter of 14 mm.
[0124] 2. Preparation of electrolyte
[0125] An equal volume of ethylene carbonate is dissolved in propylene carbonate, and then an appropriate amount of sodium perchlorate is uniformly dissolved in the mixed solvent to form a 1 mol / L electrolyte for use.
[0126] 3. Negative electrode: Use metallic sodium plate.
[0127] 4. Isolation membrane: choose glass fiber.
[0128] 5. Preparation of button battery:
[0129] Stack the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and inject the prepared electrolyte into the battery cell to complete the preparation of the button battery.
[0130] According to the test section above, the first discharge specific capacity and cycle performance of the button-type battery prepared above were measured, and the results are summarized in the following Table 1.
[0131]
[0132] It can be seen from the data in Table 1 above that the doping elements in the positive electrode active material in the form of O3 phase layered metal oxide have a significant effect on the structural properties of the positive electrode active material, such as the crystallization and the mixing degree of sodium cations; in addition, the sintering temperature and time of the positive electrode active material will also affect the structural properties, which will further affect the electrochemical properties of the sodium ion battery, especially the high-voltage discharge specific capacity and high-voltage cycle performance.
[0133] From the changes in the I(003) / I(104) values of Examples 1-5 and Comparative Examples 1-3 in Table 1, it can be seen that the O3-Na 0.85 M b Ni 0.175 Fe 0.2 Mn 0.525 O2 relative to undoped O3-Na 0.9 Ni 0.3 Mn 0.4 Fe 0.3The O2 material has more excellent structural stability, thus showing excellent comprehensive electrochemical performance, especially excellent comprehensive electrochemical performance in the high-voltage section. Therefore, this material has great potential application value as the cathode material of sodium-ion batteries.
[0134] Moreover, from the change of the I(003) / I(104) values of Examples 1-5 and Comparative Example 4 in Table 1, it can be seen that after the O3-Na 0.85 M b Ni 0.175 Fe 0.2 Mn 0.525 O2 is doped with specific metals, compared with O3-Na 0.9 Ni 0.3 Mn 0.4 Fe 0.3 The O2 material has more excellent structural stability, thus showing excellent comprehensive electrochemical performance, especially excellent comprehensive electrochemical performance in the high-voltage section, which was difficult to foresee before this application.
[0135] In addition, the sintering temperature and sintering time will also have a certain impact on the structural properties (including the crystallization of the cathode active material and the degree of sodium cation mixing) and electrical properties (the high-voltage discharge specific capacity and high-voltage cycle performance of sodium-ion batteries) of the cathode active material. The cathode active material with the best performance can be obtained by sintering at 900 °C for 20 hours.
[0136] This application also includes the following exemplary embodiments:
[0137] Embodiment 1. A cathode active material for sodium-ion batteries, which mainly contains an O3-phase layered metal oxide, and the O3-phase layered metal oxide has the following molecular formula:
[0138] Na a M b Ni c Fe d Mn e O 2±δ (Formula I)
[0139] In Formula I,
[0140] M is a metal cation different from Ni, Fe, and Mn; 0.67 < a < 1.1; 0 < b < 0.25, preferably 0.05 < b < 0.15; 0 < c < 0.3, preferably 0.05 < c < 0.25; 0 < b + c < 0.55; 0.45 < d + e < 1; and b + c + d + e = 1; 0 ≤ δ ≤ 0.1,
[0141] wherein, the metal cation is selected from Li + , Cu 2+、Zn 2+ 、Co 2+ 、Ti 4+ At least one of .
[0142] Embodiment 2. A positive electrode active material for a sodium ion battery as described in Embodiment 1, wherein the I(003) / I(104) of the O3 phase layered metal oxide in the X-ray diffraction spectrum is ≥0.62, preferably between 0.67 and 1.5, wherein I(003) represents the (003) crystal plane peak intensity of the O3 phase layered metal oxide, I(104) represents the (104) crystal plane peak intensity of the O3 phase layered metal oxide, and I(003) / I(104) reflects the degree of mixing of sodium metal cations in the O3 phase layered metal oxide.
[0143] Embodiment 3. The positive electrode active material for a sodium ion battery as described in Embodiment 1, wherein the O3 phase layered metal oxide is a space group of A hexagonal crystal system, wherein the ratio of the unit cell parameter c to the unit cell parameter a is ≥5, preferably ≥5.5.
[0144] Embodiment 4. The positive electrode active material for a sodium ion battery as described in Embodiment 1, wherein the I(003) / I(104) of the O3 phase layered metal oxide in the X-ray diffraction spectrum is ≥0.62, preferably between 0.67 and 1.5, and the O3 phase layered metal oxide is a space group of A hexagonal crystal system, wherein the ratio of the unit cell parameter c to the unit cell parameter a is ≥5, preferably ≥5.5.
[0145] Embodiment 5. The positive electrode active material for a sodium ion battery as described in any one of Embodiments 1 to 4, wherein the primary particles of the O3-phase layered metal oxide are a sheet-like structure.
[0146] Embodiment 6. The positive electrode active material for a sodium ion battery as described in Embodiment 5, wherein the grain size of the primary particles is between 0.05 micrometers and 15 micrometers, preferably between 0.1 micrometers and 5 micrometers.
[0147] Embodiment 7. The positive electrode active material for a sodium ion battery according to any one of embodiments 1 to 4, wherein the compaction density of the positive electrode active material under a pressure of 8 tons is between 1.5 g / cm 3 and 4.5g / cm 3 between, preferably between 2.5 g / cm 3 and 4g / cm 3 between.
[0148] Embodiment 8. The positive electrode active material for a sodium ion battery according to any one of embodiments 1 to 4, wherein the positive electrode active material is obtained as follows:
[0149] i) in the presence of a complexing agent and a precipitant, a Ni source and a Mn source are co-precipitated by a co-precipitation method to obtain a nickel-manganese metal salt precursor, and
[0150] ii) solid-phase sintering the nickel-manganese metal salt precursor obtained in step i) with a Na source, an Fe source and an M metal source to obtain a positive electrode active material comprising an O3-phase layered metal oxide.
[0151] Embodiment 9. The positive electrode active material for a sodium ion battery as described in Embodiment 8, wherein the sintering is carried out at a temperature of 850-920°C, preferably at a temperature of 890-910°C, more preferably at a temperature of 895-905°C, and most preferably at a temperature of 900°C.
[0152] Embodiment 10. The positive electrode active material for a sodium ion battery as described in Embodiment 8, wherein the sintering is performed for 15-25 hours, preferably for 17-22 hours, more preferably for 19-21 hours, and most preferably for 20 hours.
[0153] Embodiment 11. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, wherein the positive electrode active material is the positive electrode active material described in any one of Embodiments 1 to 10, and the battery has a charging cut-off voltage of 4.2V or higher.
[0154] Embodiment 12. The sodium ion battery of Embodiment 11, wherein the battery has an initial discharge specific capacity of 120 mAh / g at a voltage of 2.0-4.2 V and a capacity retention rate of 87% or more after 100 cycles at 1 C.
[0155] Embodiment 13. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, wherein the positive electrode active material is the positive electrode active material described in any one of Embodiments 1 to 10, and the battery has a charging cut-off voltage of 4.5V or higher.
[0156] Embodiment 14. The sodium ion battery of Embodiment 13, wherein the battery has an initial discharge specific capacity of 150 mAh / g at a voltage of 2.0-4.5 V and a capacity retention rate of 80% or more after 100 cycles at 1 C.
[0157] Embodiment 15. A battery module, characterized in that it includes a sodium ion battery according to any one of Embodiments 11 to 12 or Embodiment 13.
[0158] Embodiment 16. A battery pack, comprising the battery module according to Embodiment 15.
[0159] Embodiment 17. A device, characterized in that it includes a sodium ion battery according to any one of embodiments 11 to 12 or embodiment 13, and the sodium ion battery serves as a power source for the device; preferably, the device includes an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, an electric ship, or an energy storage system.
[0160] Although the invention has been described with reference to a number of embodiments and examples, a person skilled in the art, based on the present disclosure, will recognize that other embodiments can be designed without departing from the scope and spirit of the invention.
Claims
1. A cathode active material for a sodium-ion battery, which mainly comprises an O3-phase layered metal oxide, and the O3-phase layered metal oxide has the following molecular formula: Na a M b Ni c Fe d Mn e O 2±δ (Formula I) In Formula I, M is a metal cation different from Ni, Fe, and Mn; 0.67 < a < 1.1; 0 < b < 0.25, preferably 0.05 < b < 0.15; 0 < c < 0.3, preferably 0.05 < c < 0.25; 0 < b + c < 0.55; 0.45 < d + e < 1; and b + c + d + e = 1; 0 ≤ δ ≤ 0.1, in, The metal cation is selected from Li + , Cu 2+ 、Zn 2+ 、Co 2+ 、Ti 4+ one of; and wherein, the I(003) / I(104) of the O3-phase layered metal oxide in the X-ray diffraction spectrum is greater than or equal to 0.7 and not higher than 1.2, where I(003) represents the peak intensity of the (003) crystal plane of the O3-phase layered metal oxide, I(104) represents the peak intensity of the (104) crystal plane of the O3-phase layered metal oxide, and I(003) / I(104) reflects the degree of mixing of sodium metal cations in the O3-phase layered metal oxide.
2. The positive electrode active material for sodium ion battery according to claim 1, wherein The O3 phase layered metal oxide has a space group of A hexagonal crystal system in which the ratio of the unit cell parameter c to the unit cell parameter a is ≥5.
5.
3. The positive electrode active material for a sodium ion battery according to claim 1 or 2, wherein: The metal cation is Li + .
4. The positive electrode active material for a sodium ion battery according to claim 1 or 2, wherein The O3 phase layered metal oxide has a chemical formula of Na 0.85 Li 0.1 Ni 0.175 Fe 0.2 Mn 0.525 O2, and the I(003) / I(104) of the O3 phase layered metal oxide in the X-ray diffraction spectrum is 0.87, and the ratio of the unit cell parameter c to the unit cell parameter a is 5.
58.
5. The positive electrode active material for a sodium ion battery according to claim 1 or 2, wherein: The primary particles of the O3-phase layered metal oxide are in a flake structure.
6. The positive electrode active material for sodium ion battery according to claim 5, wherein: The grain size of the primary particles is between 0.05 μm and 15 μm.
7. The positive electrode active material for sodium ion battery according to claim 5, wherein: The grain size of the primary particles is between 0.1 μm and 5 μm.
8. The positive electrode active material for a sodium ion battery according to claim 1 or 2, wherein: The compaction density of the positive electrode active material under 8 tons of pressure is between 1.5 g / cm 3 and 4.5g / cm 3 between.
9. The positive electrode active material for a sodium ion battery according to claim 1 or 2, wherein: The compaction density of the positive electrode active material under 8 tons of pressure is between 2.5 g / cm 3 and 4g / cm 3 between.
10. A method for preparing the cathode active material for a sodium-ion battery according to any one of claims 1 to 9, the method comprising: i) In the presence of a complexing agent and a precipitating agent, by a coprecipitation method, a Ni source and a Mn source are coprecipitated to obtain a nickel-manganese metal salt precursor, and ii) The nickel-manganese metal salt precursor obtained in step i) is subjected to solid-phase sintering with a Na source, an Fe source, and an M metal source to obtain a cathode active material containing an O3-phase layered metal oxide.
11. The method of claim 10, wherein: The sintering is carried out at a temperature of 850 - 920 °C.
12. The method of claim 11, wherein: The sintering is carried out for 17 - 22 hours.
13. The method of claim 11, wherein: The sintering is carried out at a temperature of 890 - 910 °C.
14. The method of claim 11, wherein: The sintering is carried out at a temperature of 895 - 905 °C.
15. The method of claim 11, wherein: The sintering is carried out at a temperature of 900 °C.
16. The method of claim 12, wherein: The sintering is carried out for 19 - 21 hours.
17. The method of claim 12, wherein: The sintering is carried out for 20 hours.
18. A sodium-ion battery, comprising a positive electrode plate, a negative electrode plate, a separator membrane and an electrolyte disposed between the positive electrode plate and the negative electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material is the positive electrode active material according to any one of claims 1 to 17, and the battery has a charging cut-off voltage of 4.2 V or higher.
19. The sodium ion battery according to claim 18, wherein: The battery has a first discharge specific capacity of 120 mAh / g or higher at a voltage of 2.0 - 4.2 V and a capacity retention rate of 87% or higher after 100 cycles at 1C.
20. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, wherein the positive electrode active material is the positive electrode active material according to any one of claims 1 to 17, and the battery has a charge cut-off voltage of 4.5V or higher.
21. The sodium ion battery according to claim 20, wherein: The battery has an initial discharge specific capacity of 150 mAh / g or more at a voltage of 2.0-4.5 V and a capacity retention rate of 80% or more after 100 cycles at 1 C.
22. A battery module, characterized in that: Comprising a sodium ion battery according to any one of claims 18 to 19 or claim 20 or 21.
23. A battery pack, characterized in that: Comprising the battery module according to claim 22.
24. A device, characterized in that The device comprises a sodium ion battery according to any one of claims 18 to 19 or claim 20 or 21, wherein the sodium ion battery serves as a power source for the device.
25. The apparatus of claim 24, wherein the apparatus comprises an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, an electric boat, an energy storage system.